2007
DOI: 10.1007/s10620-007-8102-1
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Delays but Does Not Avoid the Need for Surgery in Treatment-Resistant Pediatric Crohn’ Disease

Abstract: The aim of this study was to review the impact of infliximab therapy on children with treatment-resistant Crohn's disease. Treatment resistance was defined as clinically active disease despite >4 months of immunosuppressive therapy. The outcome variables were time to first remission, duration of remission and the need for surgery. 24 children received 90 infusions of infliximab (16 boys; median 10.3y, range 1.0-14.4y); all had three infusions as an induction course. 17 (70.8%) achieved clinical remission, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…As in adult patients, treatment with IFX probably postpones but does not diminish the need for surgery. 33 Safety analyses showed no major adverse events in this study during the 60-week observation period. A large number of mild and uncomplicated infectious episodes were noted, which are not necessarily related to CD nor the immunomodulatory or biological therapy.…”
Section: Discussionmentioning
confidence: 58%
“…As in adult patients, treatment with IFX probably postpones but does not diminish the need for surgery. 33 Safety analyses showed no major adverse events in this study during the 60-week observation period. A large number of mild and uncomplicated infectious episodes were noted, which are not necessarily related to CD nor the immunomodulatory or biological therapy.…”
Section: Discussionmentioning
confidence: 58%
“…The use of Infliximab in children has, however, been associated with a delay in surgery rather than its avoidance 26. An additional issue in relation to the use of biologic agents in young patients with Crohn's disease is the development of antibodies to these medications, and subsequent treatment resistance 27.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing use of immunomodulators and antitumor necrosis factors may reduce the surgery rates over time. However, short-term data from Afzal et al 54 showed that despite achieving clinical remission in 70% of CD children with infliximab, 58% still required surgery within the next 12 months.…”
Section: Discussionmentioning
confidence: 99%